2022
DOI: 10.1016/j.idc.2022.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Awakening

Abstract: Synopsis The violence and victimization brought by colonization and slavery and justified for over a century by race-based science have resulted in enduring inequities for Black, Indigenous and People of Color (BIPOC) across the United States. This is particularly true if BIPOC individuals have other intersecting devalued identities. We highlight how such longstanding inequities paved the way for the disproportionate burdens of COVID-19 among the BIPOC populations across the country and provide reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…It is clear that race/ethnicity is a valid and critical risk marker for other underlying conditions affecting the complexity of COVID-19 disease, such as structural racism, discrimination and socioeconomic status, [ 70 ] lack of health care access, [ 71 ] and exposure to infectious agents related to high risk and service industry occupations [ 72 ]. Although one can never be confident that all confounding factors have been adjusted properly, Williamson et al [ 2 ] showed that ethnicity among a very large cohort in England was associated with COVID-19 outcomes, even after adjusting for socioeconomic factors.…”
Section: Discussionmentioning
confidence: 99%
“…It is clear that race/ethnicity is a valid and critical risk marker for other underlying conditions affecting the complexity of COVID-19 disease, such as structural racism, discrimination and socioeconomic status, [ 70 ] lack of health care access, [ 71 ] and exposure to infectious agents related to high risk and service industry occupations [ 72 ]. Although one can never be confident that all confounding factors have been adjusted properly, Williamson et al [ 2 ] showed that ethnicity among a very large cohort in England was associated with COVID-19 outcomes, even after adjusting for socioeconomic factors.…”
Section: Discussionmentioning
confidence: 99%
“…It is clear that race/ethnicity is a valid and critical risk marker for other underlying conditions affecting the complexity of COVID-19 disease, such as structural racism, discrimination and socioeconomic status, [70] lack of health care access, [71] and exposure to infectious agents related to high risk and service industry occupations. [72] Although one can never be confident that all confounding factors have been adjusted…”
Section: Discussionmentioning
confidence: 99%
“…Other areas of inequality included race, those with pre-existing conditions, the immunocompromised, and persons living with physical or mental disabilities. Andrasik et al [12] write that: "For most infectious diseases, including COVID-19, the most extreme burden of disease is experienced by society's most vulnerable, most often, people who experience multiple forms of social disadvantage" (p. 297).…”
Section: Covid-19mentioning
confidence: 99%